Beam Monitor Calibration for Radiobiological Experiments With Scanned High Energy Heavy Ion Beams at FAIR - Luoni, Francesca; Weber, Uli; Boscolo, Daria; Durante, Marco; Reidel, Claire-Anne; Schuy, Christoph; Zink, Klemens; Horst, Felix (Frontiers in Physics, 2020)
Precise and reliable monitoring of the particle rate is of great importance at accelerator facilities worldwide. In this article we describe the standard beam monitor calibration currently employed at the multi-purpose experimental sites Cave A and Cave M at GSI, where intense highly energetic ion beams are routinely used for a wide variety of experiments. An absolute dose-to-water measurement is performed with an air-filled ionization chamber and transferred into a calibration per primary particle. This is necessary for the raster scanning system used to enable the irradiation of extended fields, required for biophysical experiments in the research fields of particle therapy or space radiation protection. The main focus of this work is to understand through Monte Carlo simulations whether the currently used dosimetry procedure is valid for all the ion species and energies that are provided at GSI Cave A by the SIS18 synchrotron and that will be provided by the SIS100 at FAIR. With this aim the detailed geometry of the 30013 Farmer ionization chamber currently used in the cave was implemented in the transport code FLUKA and the beam quality correction factor kQ for different energies and ion species was calculated. Further details about the robustness of the calibration are investigated as well, e.g. appropriate irradiation depth of biological samples. Evidence is presented that for ions above 1 GeV/u the kQ factor decreases due to the density effect, which modifies the water-to-air stopping power ratio at relativistic energies. These findings are of particular importance for future biophysics experiments with ion beams from the SIS100 in the framework of the FAIR project. For energies in the regime of several GeV/u the constant kQ value as used in common practice should be replaced with the energy-dependent correction factor provided in this work.